Analisis Pelayanan Administrasi Kependudukan Dalam Pembuatan Akta Kelahiran Dan Kartu Keluarga Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kota Medan - Khori Ayu Tridyanthi; Nurbaiti Nurbaiti (LPPM Universitas Labuhanbatu, 2024)
The Department of Population and Civil Registration of the City of Medan is an implementing element of government affairs in the field of population administration and civil registration. The Medan City Population and Civil Registration Office is led by the Head of Service who is under and is responsible for the Mayor of Medan City through the Regional Secretariat. The purpose of this study is to analyze the Population Administration Management in Making Birth Certificates and Family Cards at the Office of the Department of Population and Civil Registration in Medan City. The research method used in this article is descriptive qualitative.